Need Analysis of Developing Digital Teaching Materials to Improve 21st Century Skills - Rima Melani Putri; Asrizal Asrizal* (Universitas Syiah Kuala, 2023)
Needs analysis is the initial study in development research. This analysis is necessary to produce the right product. The aim is to see the need digital teaching material to improve 21st century skills. The survey research method is applied with a quantitative approach. Technical analysis of data is done by processing and analyzing data using a Likert scale. The research object is related to student characteristics, student skills, and the need for using technology. The subjects of this study were 45 high school students in the city of Bukittinggi. They consisted of 13 men and 32 women. The average age ranged from 17 to 18 years. The results of the analysis found that the characteristics of students were in a good category, but the aspect of interest showed the lowest value. This is caused by the lack of learning media that can improve 21st century skills, especially in the component critical thinking and comunication. In addition, the lack of technology-based learning media, while the use of technology is needed in learning. Therefore, it is necessary to development of digital teaching materials to improve student skil